Aplikasi Evaluasi Model CIPP Pada Program Keagamaan di SMK Ma’arif 1 Kroya - Siti Musarofah; Muhammad Nurhalim; M. Hanif (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2020)
Evaluation is a tool or procedure used to find out and measure something in a predetermined manner and rules. While program evaluation is a systematic investigative activity about something valuable and valuable from an object. Program evaluation is here to provide input, considerations and decisions in determining whether a program is feasible to continue or terminate. In the study of evaluation, there are many different evaluation models, one of which is the CIPP (Context, Input, Process and Product) evaluation model. The importance of a program evaluation in educational institutions aims to determine the extent to which the educational program has been implemented. Educational institutions if there is a good and excellent program, it will make the school of quality and produce something in accordance with the objectives to be achieved. Religion has a very important role in life, therefore an educational institution needs a program that aims to create a generation that is moral, courteous, and has noble character, such as religious education and religious programs